Specific effects of EEG based neurofeedback training on memory functions in post-stroke victims. Issue 1 (December 2015) - Kober, Silvia; Schweiger, Daniela; Witte, Matthias; Reichert, Johanna; Grieshofer, Peter; Neuper, Christa; Wood, Guilherme
Abstract Background Using EEG based neurofeedback (NF), the activity of the brain is modulated directly and, therefore, the cortical substrates of cognitive functions themselves. In the present study, we investigated the ability of stroke patients to control their own brain activity via NF and evaluated specific effects of different NF protocols on cognition, in particular recovery of memory. Methods N  = 17 stroke patients received up to ten sessions of either SMR (N  = 11, 12–15 Hz) or Upper Alpha (N  = 6, e.g. 10–12 Hz) NF training.N  = 7 stroke patients received treatment as usual as control condition. Furthermore, N  = 40 healthy controls performed NF training as well. To evaluate the NF training outcome, a test battery assessing different cognitive functions was performed before and after NF training. Results About 70 % of both patients and controls achieved distinct gains in NF performance leading to improvements in verbal short- and long-term memory, independent of the used NF protocol. The SMR patient group showed specific improvements in visuo-spatial short-term memory performance, whereas the Upper Alpha patient group specifically improved their working memory performance. NF training effects were even stronger than effects of traditional cognitive training methods in stroke patients. NF training showed no effects on other cognitive functions than memory. Conclusions Post-stroke victims with memory deficits could benefit from NF training as much as healthy controls. The used NF training protocols (SMR, Upper Alpha) had specific as well as unspecific effects on memory. Hence, NF might offer an effective cognitive rehabilitation tool improving memory deficits of stroke survivors.